2019
DOI: 10.1186/s13064-019-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish prdm12b acts independently of nkx6.1 repression to promote eng1b expression in the neural tube p1 domain

Abstract: Background Functioning of the adult nervous system depends on the establishment of neural circuits during embryogenesis. In vertebrates, neurons that make up motor circuits form in distinct domains along the dorsoventral axis of the neural tube. Each domain is characterized by a unique combination of transcription factors (TFs) that promote a specific fate, while repressing fates of adjacent domains. The prdm12 TF is required for the expression of eng1b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…circuits, V1 inhibitory neurons ensure proper swim frequency during fast swim movements; ablation of these neurons [47] or loss through mutation of prdm12b ( [45] and our results) results in reduced swim cycle frequency and prolonged bend duration. Based on Kv1.1's previous shown role in regulating neuron excitability [65][66][67], we predict loss of kcna1a induces hyperactivity in specific neurons, making it unlikely that loss of kcna1a in V1 neurons leads to the exaggerated response phenotype.…”
Section: Plos Geneticssupporting
confidence: 57%
See 2 more Smart Citations
“…circuits, V1 inhibitory neurons ensure proper swim frequency during fast swim movements; ablation of these neurons [47] or loss through mutation of prdm12b ( [45] and our results) results in reduced swim cycle frequency and prolonged bend duration. Based on Kv1.1's previous shown role in regulating neuron excitability [65][66][67], we predict loss of kcna1a induces hyperactivity in specific neurons, making it unlikely that loss of kcna1a in V1 neurons leads to the exaggerated response phenotype.…”
Section: Plos Geneticssupporting
confidence: 57%
“…Zebrafish prdm12b was previously identified in a screen for genes that express in the nervous system [ 44 ]. Morpholinos targeting prdm12b [ 27 ] and a prdm12b CRISPR mutation [ 45 ] result in larvae with aberrant, exaggerated touch behaviors, similar to the exaggerated acoustic startle response we observe in the p419 mutants. prdm12b is required for development of engrailed 1b positive, V1 interneurons in the spinal cord [ 27 ].…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…(H4K20me3, G9a/H3K9me2) 30,31 , PRDM12 [32][33][34][35] and PRDM14 (EZH2/K27me3), 36,37 , suggesting that PRDMs are able to recruit histone "writers" through protein-protein interactions. Furthermore, PRDMs are able to recruit histone "erasers" (i.e.…”
Section: Pr Domain: Structural Aspectsmentioning
confidence: 99%
“…Another gene implicated in neurogenesis in the neural tube is prdm12b . Using CRISPR/Cas9 to generate two fish lines carrying frameshift mutations in prdm12b, authors revealed that eng1b expression was suppressed in V1 interneurons, leading to defective Mauthner cell-dependent locomotion and embryonic lethality [ 100 ].…”
Section: Crispr Applications In Neural Diseasesmentioning
confidence: 99%